Authenticity in Language Learning: A Study of Language Materials in Public High Schools - Domogen, Jevera Cawilan (OKARA: Jurnal Bahasa dan Sastra, 2023)
Instructional materials are paramount in effecting language instruction. However, there are contextual issues related to the use and selection of these materials. This study focused on authentic language instructional materials in public secondary schools in the Philippines. This study employed a mixed-methods research approach. This study concludes that internet-based authentic language instructional materials are inadequate in language instruction, showing limitations on the capacity of the school and the language teachers to provide adequate internet-based materials; there are concerns about using authentic language instructional materials that hinder learners' authentic response and comprehension to authentic language instructional materials, and there were measures to overcome the concerns which could develop authentic language instructional materials into the ideal learning materials. It is recommended that language teachers select resources according to the learners' unique requirements, proficiency levels, cultural contexts, and educational contexts. The participation of learners in the selection process and activity design is crucial to ensure the materials are engaging and culturally pertinent. To effectively address the challenges associated with using these resources, a collaborative approach is recommended, involving teachers, students, and other stakeholders in implementing the suggested solutions.